The Nexus Between Environmental Management Accounting Practices and Financial Sustainability of Cement and Mining Companies in South Africa - Thomas NYAHUNA; Mishelle DOORASAMY (International Journal of Environmental, Sustainability, and Social Science, 2023)
The main purpose of the study is to investigate the relationship between environmental management accounting practices (EMAP) and financial performance of South African cement and mining companies. To attain the major objective of the research, three hypotheses were tested based on data from 45 JSE-listed cement and mining companies from 2010 to 2021. Multiple regression analysis with the assistance of IBM SPSS Statistics 24was also used to test the hypotheses. The study found that two accounting measures namely return on assets and net profit margin had no significant relationship with EMAP. However, the study also revealed that one accounting based measure namely return on equity had a positive and significant relationship with EMAP. This signifies that EMA is still at its primary stages in South Africa. In addition, the results also suggest that EMA is important to accomplish sustainability. The results provide managers with empirical evidence of EMAP that increases financial sustainability in the context of an emerging economy such as South Africa.